Rancang Bangun Mesin Pembusa dengan Variasi Bibit Pembusa - An-Nisa Magnolia; nurcahya nugraha; rizal nazarudin nazarudin; ferly citra ardiansyah (Universitas Muhammadiyah Metro, 2026)
This study aims to design and develop a foam generator for the production of lightweight construction materials. The primary focus is to analyze the impact of varying ratios between water and foaming agent on the density of the foam produced. The developed device is expected to produce stable foam with precise control over its density and bubble size. The research involves designing, assembling, and testing different mixtures of foaming agents. The results show that increasing the volume of the foaming agent leads to higher foam density, smaller bubble size, and closer spacing between bubbles. The optimal ratio found in this study is 1000 ml foaming agent to 19000 ml water, which produced the densest and most homogeneous foam. At this ratio, the foam exhibits smaller bubbles and tightly packed distribution, resulting in a material with sufficient structural strength and low density. The findings provide a foundation for further development of more efficient and stable foam generators, offering potential for producing environmentally friendly and cost-effective lightweight construction materials.